Prospecting for Oleaginous and Robust Chlorella spp. for Coal-Fired Flue-Gas-Mediated Biodiesel Production - Bohwa Kim; Ramasamy Praveenkumar; Eunji Choi; Kyubock Lee; Sang Goo Jeon; You-Kwan Oh (Energies, 2018)
Prospecting for robust and high-productivity strains is a strategically important step in the microalgal biodiesel process. In this study, 30 local strains of Chlorella were evaluated in photobioreactors for biodiesel production using coal-fired flue-gas. Three strains (M082, M134, and KR-1) were sequentially selected based on cell growth, lipid content, and fatty acid composition under autotrophic and mixotrophic conditions. Under autotrophic conditions, M082 and M134 showed comparable lipid contents (ca. 230 mg FAME [fatty acid methyl esters derived from microalgal lipids]/g cell) and productivities (ca. 40 mg FAME/L·d) versus a reference strain (KR-1) outdoors with actual flue-gas (CO2, 13%). Interestingly, under mixotrophic conditions, M082 demonstrated, along with maximal lipid content (397 mg FAME/g cell), good tolerance to high temperature (40 °C). Furthermore, the fatty acid methyl esters met important international standards under all of the tested culture conditions. Thus, it was concluded that M082 can be a feedstock of choice for coal-fired, flue-gas-mediated biodiesel production.